PKM konstruksi alat tanam padi untuk persawahan tadah hujan - Ahmad Syawaluddin; Hamsu Abdul Gani; Bakhrani A. Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The problem of the Community Partnership Program (PKM) is to: (1) Rainfed Farmer Groups (partners) do not knowabout the construction of upland rice planting tools that are water-efficient, practical, efficient, save time and energy, (2) Farmers'groups rain (partners) are not skilled at designing, forming a frame, making a frame, assembling the framework of theconstruction of rice planting tools that are water-efficient, practical, efficient, saving time and energy, (3) rainfed farming groups(partners) unskilled planting equipment operators upland rice models that are water efficient, practical, efficient, save time andenergy. Solutions for the Community Partnership Program (PKM) are: (1) Increasing the knowledge of rainfed farmer groups(partners) about the construction of upland rice planting tools that are water-efficient, practical, efficient, saving time and energy,(2) Improving the skills of farmer groups rainfed (partner) about designing, forming a frame, making a frame, assembling a framefor the construction of the gogo-style rice planting tool that is water saving, practical, efficient, saving time and energy, (3)Improving the skills of a rainfed farmer group (partner) about the operation of the tool planting upland rice models that are waterefficient, practical, efficient, save time and energy. The target audience is a rainfed farmer group (partners) who have difficultygrowing rice (the target audience is trained directly). The method used in the delivery of counseling material is the lecture,discussion and question and answer method, for the training used the demonstration method. The output targets to be achievedare as follows: (1) Rainfed farmer groups (partners) can find out about the construction of upland rice planting tools that arewater-efficient, practical, efficient, save time and energy, (2) Rainfed farmer groups ( partner) can skillfully design, form a frame,make a frame, assemble a framework for the construction of the rice planting equipment model that is water-efficient, practical,efficient, saving time and energy, (3) Rainfed farmers group (partners) can skillfully operate a model of rice planting equipmentgogo that saves water, is practical, efficient, saves time and energy.